Avaliação da aprendizagem no ensino superior: significados e modos de ação de docentes do curso de Pedagogia - Mouraes, Rosilene Silva de (2022)
This research is linked to the Teaching-Learning Processes research line of the Graduate Program in Education, Federal University of Paraíba (CE/PPGE/UFPB) and its general objective is to investigate the meanings and ways of acting that shape the assessment practices of professors in the Undergraduate Program of Pedagogy at one of the campuses of the Federal University of Paraíba. Learning assessment plays an important role in the teaching and learning process and, as we place the focus on the undergraduate program of Pedagogy, we can discuss how undergraduate courses that train students to become teachers prepare professionals to work in education, assuming that their training experiences, including those related to assessment, contribute to their pedagogical instruction. This research relies on an instrumental qualitative case study; it is based on an exploratory study and it is inspired by the epistemological approach of Symbolic Interactionism, since we believe that the way professors understand assessment is not the result of thinking in isolation of the relationships they establish with the world; rather, it derives from the interaction with others, mediated by socially structured meanings. As for the techniques for collecting the data, we adopted the interview and semi-structured questionnaire, given the context of social isolation imposed by the COVID-19 pandemic. The data were collected online, thus following the guidelines provided for in Official Memorandum no. 2/2021/CONEP/SECNS/MS. The type of data analysis chosen for the research was Content Analysis, as in Bardin (2016). To contribute to the improvement of assessment practices at UFPB's Undergraduate Program of Pedagogy, the theoretical basis of the research relied on conceptual categories that include Learning Assessment, studies in University Pedagogy, and studies in Didactics in Higher Education. The results achieved indicate that the learning assessment as developed in the Undergraduate Program of Pedagogy, the locus of the research, is intersected by meanings which, in turn, are produced and/or acquired by professors, specifically, through the interaction with other people in their training and professional work contexts. Among the learned content, participants say they conduct a formative and/or continuous assessment practice and understand that assessment leads to a reflection of their teaching practice. In addition, the research concluded that such meanings were interpreted and transformed, that is, the professors controlled their ways of acting. Regarding their assessment practice, the professors under study are at the symbolic interaction level, as they interpret another person’s action and they select/modify/avoid/transform it.